Audit Committee Composition and Auditor Reporting - Carcello, Joseph V.; Neal, Terry L. (The Accounting Review, 2000)
This study examines the relation between the composition of financially distressed firms' audit committees and the likelihood of receiving going-concern reports. For firms experiencing financial distress during 1994, we find that the greater the percentage of affiliated directors on the audit committee, the lower the probability the auditor will issue a going-concern report. These results support regulators' concern about financial-reporting quality and the recent calls for more independent audit committees.